The Influence of Leadership Style and Organizational Culture on Employee Performance Through Employee Satisfaction as An Intervening Variable in PG GEMPOLKREP-PTPN X - Imaniar Cahyani; Eddy Yunus (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2022)
Abstract.The existence of a new leader with a young age in recent years has given color to the leadership style at PTPN X. In the same period, the board of directors reconstructed and reintroduced the vision, mission and culture of the organization. The unachieved production potential per hectare and milling capacity have become evaluation material for management to achieve added value. Therefore this study aims to analyze the influence of leadership style and organizational culture on the performance of PG Gempolkrep-PTPN X employees, and analyze it through job satisfaction as an Intervening Variable. This research was conducted using a quantitative approach with a survey assessment method using a questionnaire as a data collection tool. The research sample used was purposive sampling, namely 34 employees from the leadership of PG Gempolkrep-PTPN X. Data analysis is based on data obtained from internal company sources and the results of questionnaires that have been distributed to respondents. The procedure carried out is to assess the results of the questionnaire and process them using the SEM-PLS method to then be analyzed using the partial least squares analysis technique using smartPLS. The results of the study show that leadership style and organizational culture have a significant effect on employee performance, leadership style and organizational culture have a significant effect on employee job satisfaction, and job satisfaction has a significant effect on employee performance, which means job satisfaction can mediate the influence of leadership style and organizational culture. on employee performance. Keywords: Leadership Style; Organizational Culture; Employee Performance; Job Satisfaction